2021
DOI: 10.1029/2021jb022355
|View full text |Cite
|
Sign up to set email alerts
|

GPS Imaging of Global Vertical Land Motion for Studies of Sea Level Rise

Abstract: Points 1. GPS stations constrain trends, seasonal and non-seasonal variability in vertical land motion (VLM) across the Earth's land surface.2. GPS Imaging provides robust VLM estimates and more completely assesses spatial and temporal signal uncertainty and variability.3. Average VLM is positive on the land areas and subsidence elsewhere, but average non-GIAVLM is subsidence on average and uplift elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 108 publications
(176 reference statements)
8
59
0
Order By: Relevance
“…Our finding of long‐term subsidence in the sector of coastal East Antarctica west of Totten Glacier builds on previous studies that have analyzed earlier records from DAV1 and BHIL, and MAW1 650 km to the west of DAV1, indicating subsidence or marginal amounts of uplift along this coastline (Argus et al., 2014; Hammond et al., 2021; Martín‐Español et al., 2016; Thomas et al., 2011). Liu et al.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding of long‐term subsidence in the sector of coastal East Antarctica west of Totten Glacier builds on previous studies that have analyzed earlier records from DAV1 and BHIL, and MAW1 650 km to the west of DAV1, indicating subsidence or marginal amounts of uplift along this coastline (Argus et al., 2014; Hammond et al., 2021; Martín‐Español et al., 2016; Thomas et al., 2011). Liu et al.…”
Section: Discussionsupporting
confidence: 85%
“…The average uncertainties from our approach at GPS and TG sites were 0.65 and 0.71 mm/yr, respectively, comparable with 0.83 and 0.87 mm/yr inferred from Hector-derived (at GPS) and GPS-Krig (at TG) uncertainties, respectively. The GPS-inferred VLM field showed that the Australian plate is largely subsiding with weighted mean rates of -0.10, -0.38, -0.95 and -0.62 mm/yr in the NW, NE, SW and SE regions, respectively, in general agreement with previous GPS estimates of subsidence (Hammond et al, 2021;Riddell et al, 2020). The estimates at TGs revealed localized VLM trends around the continent that are not completely consistent with the GPS-Krig interpolations.…”
Section: Linear Vlmsupporting
confidence: 78%
“…GPS observations of VLM across Australia suggest the continent is subsiding overall (Hammond et al, 2021;King et al, 2012;Riddell et al, 2020). Recent work by Riddell et al (2020) using GPS time series showed the widespread pattern of subsidence cannot be fully explained by GIA.…”
Section: Introductionmentioning
confidence: 99%
“…It would be impossible to obtain sufficient data without complementary space-geodetic techniques. For instance, non-linear VLM can be estimated from global navigation satellite system (GNSS) station time series [9][10][11] and interferometric synthetic aperture radar (InSAR) analysis [7,12,13]. Due to the non-linearity of the VLM, however, observed motions cannot be extrapolated to the past or future.…”
Section: Introductionmentioning
confidence: 99%
“…The Fennoscandian Shield (including the whole Baltic Sea region) in Northern Europe is an area of a relatively low temporal VLM variability [11]. The primary cause for VLM is GIA [16,26,27], whereas the contribution from seasonal and nonseasonal velocity variability to VLM is typically modest [11]. Furthermore, the estimated current GIA deceleration of 0.002 mm/y 2 can be considered negligible [28].…”
Section: Introductionmentioning
confidence: 99%